1α,25(OH)2D3-glycosides from Solanum glaucophyllum leaves extract induce myoblasts differentiation through p38 MAPK and AKT activation - Irazoqui, Ana Paula (2018)
We have previously shown that Solanum glaucophyllum leaf extract (SGE) increases VDR protein levels and promotes myoblast differentiation. Here, we investigated whether p38 MAPK and AKT are involved in SGE actions. Cell-cycle studies showed that SGE prompted a peak of S-phase followed by an arrest in the G0/G1-phase through p38 MAPK. Time course studies showed that p38 MAPK and AKT phosphorylation were statistically increased by SGE (10 nM) or synthetic 1α,25(OH)2D3 (1 nM) treatment. Furthermore, p38 MAPK and AKT inhibitors, SB203580 and LY294002 respectively, suppressed myoblasts fusion induced by SGE or synthetic 1α,25(OH)2D3. We have also studied differentiation genes by qRT-PCR. myoD1 mRNA increased significantly by SGE (24–72 h) or 1α,25(OH)2D3 (24 h) treatment. mRNA expression of myogenin also increased upon SGE or 1α,25(OH)2D3 treatment. Finally, MHC2b mRNA expression, a late differentiation marker, was increased significantly by both compounds at 72 h compared to control. Taken together, these results suggest that SGE, as synthetic 1α,25(OH)2D3, promotes myotube formation through p38 MAPK and AKT activation